2009
DOI: 10.1017/s1047951109004004
|View full text |Cite
|
Sign up to set email alerts
|

Complication of surgery for scoliosis in children with surgically corrected congenital cardiac malformations

Abstract: The surgical and postoperative complications in these patients depend on the specific cardiac lesion. A multidisciplinary team with experience in the treatment of congenitally malformed hearts is essential for appropriate management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…This finding appears to suggest that postoperative complications are a significant problem for scoliotic patients with surgically corrected CCMs in clinical practice. Our complication rate was noted to be similar to earlier published data, 11 but the complications were relatively mild and reversible. No deaths occurred in the perioperative period within our cohort as a result of postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding appears to suggest that postoperative complications are a significant problem for scoliotic patients with surgically corrected CCMs in clinical practice. Our complication rate was noted to be similar to earlier published data, 11 but the complications were relatively mild and reversible. No deaths occurred in the perioperative period within our cohort as a result of postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
“…1,11 Pérez-Caballero et al reported that 1 patient (6%) died in the immediate postoperative period due to hypovolemic shock caused by massive bleeding. 11 Bitan et al came to a similar conclusion in another series of 26 patients in which 2 patients died (7.7%), with another 2 developing severe complications (7.7%). 1 However, in the present study, no deaths occurred in the perioperative period and no serious complications were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a cardiac abnormality is not a contraindication to surgical scoliosis correction [9,11] but is important to understand the nature and severity of the abnormality to assess operative risk and optimize patients from a medical and surgical standpoint [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation is generalized to all preoperative noncardiac surgery evaluations and is not specific for children with AIS undergoing scoliosis correction. In patients with AIS, there is concern for undiagnosed and underlying cardiac abnormalities that may increase operative risk [3,[5][6][7][9][10][11]13].…”
Section: Introductionmentioning
confidence: 99%
“…Los pacientes con formas de escoliosis no idiopática presentan mayor riesgo de complicaciones, particularmente hemorrágicas (coagulopatías) y respiratorias, por lo que debe sopesarse el riesgo-beneficio de la corrección quirúrgica 7 . También la mejora pronosticada en la calidad de vida ha de balancearse cuidadosamente frente al riesgo de la cirugía, sobre todo en pacientes con enfermedad neuromuscular progresiva con esperanza de vida limitada 8,9 . La lesión medular más frecuente es la isquémica, causada por la distracción/rotación vertebral o la compresión medular directa por el material de osteosínte-sis (barras, tornillos, alambres, etc.).…”
Section: Introductionunclassified